2011
DOI: 10.2147/cmr.s12700
|View full text |Cite
|
Sign up to set email alerts
|

Six-month gonadotropin releasing hormone (GnRH) agonist depots provide efficacy, safety, convenience, and comfort

Abstract: Two different 6-month GnRH agonist depot formulations approved for palliative treatment of advanced and metastatic prostate cancer in the United States – leuprolide acetate 45 mg and triptorelin pamoate 22.5 mg – provide patients with efficacy and safety comparable to those of existing 1-, 3-, and 4-month GnRH agonist depots. However, the 6-month formulations can increase patient convenience, comfort, and compliance by reducing the number of physician visits and injections required. At the conclusion of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…Perceived advantages of 6-monthly injections included less discomfort/pain, better quality of life, fewer reminders of the disease, and greater ability to undertake activities without restriction [Schulman, 2007]. The findings of our study also support recent published data showing that 6-month formulations can increase patient convenience, comfort and compliance by reducing the number of physician visits and injections required [Crawford and Phillips, 2011].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Perceived advantages of 6-monthly injections included less discomfort/pain, better quality of life, fewer reminders of the disease, and greater ability to undertake activities without restriction [Schulman, 2007]. The findings of our study also support recent published data showing that 6-month formulations can increase patient convenience, comfort and compliance by reducing the number of physician visits and injections required [Crawford and Phillips, 2011].…”
Section: Discussionsupporting
confidence: 86%
“…To date, clinical trials have shown that LHRH agonists are generally well tolerated, with generally mild side effects stemming from testosterone suppression, and a very low rate of withdrawal due to adverse events [De Jong et al 2007;Crawford and Phillips, 2011]. The high proportion of patients renewing prescriptions at 3 or 6 months and 12 months in our study may confirm this low withdrawal rate.…”
Section: Discussionsupporting
confidence: 69%
“…This required daily visits to the oncologist or urologist and greatly increased the chance of adverse effects, such as injection site reactions and injection site pain, but also made patient compliance with therapy more difficult 9. Over the last 20 years, extended release formulations of 1, 3, 4, and 6 months have been developed, significantly increasing patient acceptance to therapy and easing treatment burdens for physicians.…”
Section: Therapeutic Backgroundmentioning
confidence: 99%
“…Even though the patient reported advantage of the 3 M LHRH agonist was the high satisfying quality of medical follow-up, the 6 M formulation had the advantages of flexibility and the freedom from worrying about their cancer for up to 6 months. Among the advantages reported for the 6 M depot were reduced anxiety, decreased emotional burden, improved flexibility with scheduling, less frequent injections, improved comfort, fewer doctor visits, decreased site reactions, decreased cost, fewer missed visits and, in theory, decreased risk of breakthrough 31. In Germany the long dosing interval of 6 M leuprolide was the main reason given by urologists for making the prescribing decision with regard to the hormone deprivation therapy 32.…”
Section: Introductionmentioning
confidence: 99%